Post-traumatic radicular cyst involving multiple anterior Teeth: Open apex management and surgical enucleation – A case report - B. Doumari; S. Dhoum; Z. EL Hajjioui; M. Jabri (Advances in Oral and Maxillofacial Surgery, 2025)
Radicular cysts are the most common inflammatory odontogenic cysts, typically arising from chronic periapical infection following pulp necrosis. Post-traumatic radicular cysts involving immature teeth with open apices are uncommon and present unique clinical challenges due to incomplete root formation. This case report describes the management of a large post-traumatic radicular cyst affecting multiple maxillary anterior teeth (teeth 11, 12, and 13) in a 27-year-old patient, discovered incidentally during routine radiographic examination.Clinical examination revealed pulp necrosis and an open apex on tooth 11, with teeth 12 and 13 also non-vital. Radiographs and CBCT confirmed a well-demarcated radiolucent lesion with buccopalatal expansion and cortical bone resorption, consistent with a radicular cyst. Treatment included conventional root canal therapy for teeth 12 and 13, and apexification with Biodentine for tooth 11. Surgical enucleation of the cyst was performed via a full-thickness mucoperiosteal flap, achieving complete removal of the lesion.Biodentine, a bioactive calcium silicate-based material, was used to create an apical plug, promoting hard tissue formation and providing a reliable apical barrier, thus facilitating root canal obturation in the immature tooth. Histopathology confirmed an inflammatory radicular cyst. At 13-month follow-up, the patient was asymptomatic, with radiographic evidence of significant bone regeneration, although a residual bony defect remained. Long-term follow-up was recommended to monitor complete healing and prevent recurrence.This case highlights the importance of early diagnosis and a multidisciplinary approach combining modern endodontic materials and surgical intervention in managing post-traumatic radicular cysts involving open apex teeth, ultimately preserving tooth structure and function.